Design and simulation of MEMS piezoelectric vibration energy harvesters with centre mass block. (7th April 2020) - Wang, Lu; Lu, Dejiang; Zhang, Shenrong; Li, Zhikang; Xia, Yong; Luo, Yunyun; Zhao, Libo; Jiang, Zhuangde
MEMS-based piezoelectric vibration energy harvesters (MEMS-PVEHs) with center mass block are designed with the overall size 10 × 10 × 2 mm 3, two prototypes including piezoelectric unimorph and bimorph beams are used respectively. This paper studies the characteristics of MEMS-PVEHs by modeling and simulation in COMSOL. Their eigenfrequencies are analyzed firstly, their optimal piezoelectric outputs are explored by changing excitation frequency and load resistance secondly, then the piezoelectric unimorph and bimorph beams are compared finally. The simulation results show that the optimal excitation frequency is slightly higher than the eigenfrequency, and the maximum piezoelectric power of the PVEH can be obtained only when the appropriate excitation frequency and load resistance are selected, and the power generation efficiency is 0.5. It has little difference between unimorph and bimorph to improve the MEMS-PVEH piezoelectric output. Finally, the piezoelectric unimorph with double opposite electrodes is designed based on the MEMS fabrication process.